(NwIKTOR cOJ I GRUPPA (B"(Nkino(B" (NpAMQTNYJ AL_BOMs - (Nw(B.(NkALGINs ((NmOSKWAs (Nasts, 2018)
(NwMESTE S GIBEL_@ wIKTORA cOQ(B-(NLIDERA GRUPPY kino ZAKON^ILAS_ \POHA WELIKIH GEROEW RUSSKOGO ROKA(B,(NON BYL POSLEDNIM IZ TAKOWYH(B.s